GENDER DISCRIMINATION TOWARD JOSEY AIMES AS THE MAIN CHARACTER IN NORTH COUNTRY FILM - Febry Viona Caroline; M. Natsir; Nasrullah Nasrullah (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACTThe purpose of this research is to find out the kinds of gender discrimination toward Josey in North Country film. Further, the other purpose of this research is to identify Josey’s responses against gender discrimination as depicted in the film. In this research, the researcher focuses on examining kinds of gender discrimination by using Sheila McLean’s theory about kinds of gender discrimination and also focuses on what Josey’s responses against gender discrimination that happened to her in North Country film by using Feagin and Sikes’s theory of responses. Furthermore, the researcher uses qualitative-descriptive research and Miles and Huberman’s data analysis. In this film, the researcher finds there are four kinds of gender discrimination that have appeared in the film. The kinds of gender discrimination are subordination, marginalization, stereotype, and violence. In addition, those kinds of gender discrimination that happened toward Josey made Josey act three kinds of responses toward it. The three responses that acted by Josey in the film are withdrawal, resigned acceptance, and verbal confrontation.Keywords: gender discrimination, sheila mclean’s kinds of gender discrimination, feagin and sikes’s kinds of responses, north country. ABSTRAK Penelitian ini bertujuan untuk mengetahui jenis-jenis diskriminasi gender terhadap Josey dalam film North Country. Selanjutnya, tujuan lain dari penelitian ini adalah untuk mengidentifikasi tanggapan Josey terhadap diskriminasi gender seperti yang digambarkan dalam film tersebut. Dalam penelitian ini, peneliti berfokus untuk mengkaji jenis-jenis diskriminasi gender dengan menggunakan teori Sheila McLean tentang jenis-jenis diskriminasi gender dan berfokus pada apa tanggapan Josey terhadap diskriminasi gender yang terjadi padanya dalam film North Country dengan menggunakan teori tanggapan Feagin dan Sikes. Selanjutnya, peneliti menggunakan penelitian deskriptif kualitatif dan analisis data Miles and Huberman. Dalam film ini, peneliti menemukan empat jenis diskriminasi gender yang muncul dalam film tersebut. Jenis-jenis diskriminasi gender adalah subordinasi, marginalisasi, stereotip, dan kekerasan. Selain itu, jenis-jenis diskriminasi gender yang terjadi pada Josey membuat Josey melakukan tiga macam tanggapan terhadapnya. Tiga tanggapan yang ditunjukkan oleh Josey dalam film tersebut adalah penarikan diri, penerimaan pasrah, dan konfrontasi verbal.Kata Kunci: diskriminasi gender, jenis-jenis diskriminasi gender sheila mclean, jenis respon feagin dan sikes, north country